Context Specific Complementary Feeding Recommendations for Children in Pakistan Based on Secondary Analysis of National Complementary Feeding Assessment and Pakistan Demographic Health Survey 2018 - Shuja Saba; Khan Wisal; Mahmood Hana; Abbasi Saleem; Yahya Sheraz Syed; Alain Ategbo Eric (International Journal of Nutrition, 2023)
Background In Low Middle-Income Countries (LIMCs), malnutrition, especially undernutrition is one of the leading causes of childhood mortality and morbidity. Poor complementary feeding practices are among the most notable contributors to poor nutritional indicators in children under five. This article provides an output of secondary data analysis of the Cost of Diet (CoD) and Optifood component of National Complementary Feeding Assessment conducted by UNICEF Pakistan along with Pakistan Demographic Health Survey (PDHS) 2018. Methods For correlation of Optifood data and CoD data with PDHS data of CF, GraphPad software, MS Excel was used along with manual quantifications. The analysis of DHS-2018 data was conducted using STATA software. Univariate analysis included comparison of categorical variables i.e. various individual, household and community level parameters with that of outcome variables of minimum dietary diversity (MDD), minimum meal frequency (MMF) and minimum dietary diversity (MAD) using chi-square test. Findings The overall rate of MMF was 56.6% among children of 6-23 months of age with MDD in 18.6% and MAD in 13.8% of children. Percentage of annual cost spent on nutritious diet for MDD, MMF and MAD varies from 27.86% to 43.08% across all the provinces. Children aged 6–8 months and 9–11 months often consumed infant milk and cereals, while children aged 12–23 months often consumed eggs and grain products. Consumption of dairy products was highest in Punjab, Sindh, AJK, and Islamabad, that of grains roots and tubers was highest in KPK, FATA and GB. Conclusion Considering CF practices in Pakistan are inadequate as indicated by poor MDD, MMF, and MAD, therefore it is imperative that a holistic approach using both communication and non-communication based interventions is to be employed through active stakeholder engagement.
Keywords: Malnutrition